Religious practices, COVID-19 and peasantry: a two-part analysis of the pandemic from an extension project - Álida Angélica Alves Leal; Luiz Paulo Ribeiro (Universidade Federal do Norte do Tocantins, 2020)
This paper analyzed the repercussions of the COVID-19 pandemic on religious practices of peasant subjects and rural communities in which students of the Degree in Rural Education of the Faculty of Education of the Universidade Federal de Minas Gerais (LECampo/FaE UFMG) work and residency. This is an extract from an investigation that is linked to the extension project "The people of the countryside and the COVID-19 pandemic", created in April 2020. The methodological paths of the investigation consisted of the application of questionnaires with closed questions and open, answered by 36 students in the first stage (April/May 2020) and by 46 students in the second stage (July 2020). The data were analyzed by means of categorical content analysis. The results point to repercussions that relate to the following categories: a) socialization/sociability; b) interruption of activities in religious spaces; c) modes of remote participation in religious activities; d) hogar as a privileged place for remote religious practices; e) return from presential activities in collective religious spaces; f) relationship between pandemic, faith, punishment and divine protection.